The role of brain mechanisms in diabetic peripheral neuropathy: recent advances and comprehensive analysis - Wei, Min; Jiang, Ye; Shou, Jiayin; Xing, Guogang; Li, Min (Frontiers in Cellular Neuroscience, 2025)
Diabetic peripheral neuropathy (DPN), a prevalent and debilitating complication of diabetes, involves complex interactions between peripheral nerve damage and central nervous system (CNS) dysfunction. While traditional research has focused on peripheral and spinal mechanisms, emerging evidence highlights that the brain plays a critical role in the development of painful DPN. This review synthesizes recent advances from neuroimaging, spectroscopy, and preclinical studies to delineate structural, functional, and neurochemical alterations in the central nervous system associated with DPN. Patients exhibit cortical thinning, subcortical atrophy, and disrupted connectivity in sensory, affective, and cognitive networks, accompanied by metabolic imbalances and excitatory–inhibitory neurotransmitter shifts. Preclinical models further implicate maladaptive plasticity, microglial activation, and region-specific astrocytic responses in amplifying central sensitization and pain chronicity. These mechanistic insights underscore the central nervous system as a therapeutic target. Non-invasive neuromodulation techniques, such as repetitive transcranial magnetic stimulation, and brain-directed pharmacological strategies show promising but preliminary benefits in alleviating neuropathic pain. Understanding the interplay between peripheral injury and brain dysfunction in DPN not only broadens the conceptual framework of its pathophysiology but also provides a foundation for developing novel interventions aimed at restoring central network balance and improving patient outcomes.